PENGARUH NPL, LDR, CAR DAN BOPO TERHADAP PROFITABILITAS BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA (PERBANDINGAN BANK PEMERINTAH DAN BANK SWASTA) - Tanto, Tanto (MABIS, 2012)
This research is performed in order to test the influence of the variable Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR) and BOPO toward Return on Asset (ROA). The data is based on publicity Indonesia Banking Directory since 2007 to 2010 and fulfill minimum CAR criteria. Obtained by amount sample as much 30 bank within 5 go public national bank and 25 go public private bank. Analysis technique used is doubled regression with smallest square equation and hypothesis test use t-statistic to test coefficient of regression partial. From the result of analysis indicate that only data BOPO in partial significant toward ROA in go public national bank, but NPL, LDR and BOPO in partial significant toward ROA in go public private bank. Chow test result show 3,823 bigger than 1,96 so there is a significant difference in the effect of the influence of four independent variables on ROA in go public national bank and go public private bank.